Advanced technologies for microfinance : solutions and challenges - Ashta, Arvind (Hershey, PA : Business Science Reference, 2011)
'This book offers research on the microfinance movement that is providing poor people around the world an opportunity to take responsibility for their lives by providing them complementary elements such as financial capital and guidance'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Microfinance; Technological innovations